Formation Of CuAlO2 Thin Films By Ultrasonic Spray Pyrolysis For Photodiode Applications - Suhariadi, Iping (2011)
CuAlO2 is a p-type oxide which is transparent. When coupled with an n-type material, a p-n junction can be created and can be used in many interesting optical and electronic applications. Smooth, crack free and homogenous CuAlO2 film was produced by chemical solution deposition process via ultrasonic spray pyrolysis (USP) technique on a cleaned n-type Si substrate. The precursor solution used was comprised of a mixture of Cu(NO3)2.3H2O and Al(NO3)3.9H2O. The deposition parameter influences the film properties are the flow rate of carrier gas, nozzle-substrate distance, substrate‘s temperature and Cu to Al ratio was studied thoroughly.